Pengembangan Pemahaman Literasi Ekonomi Syariah di Perpustakaan Berbasis Inklusi Sosial Sahwahitasawangan Kabupaten Magelang - Herliana Rizki Yati; Damar Irsyad Ustadz; Wahyu Achmad Pamuji; Qurrotul Aini; Yeny Fitriyani (Jurnal Rekoginisi Ekonomi Islam, 2022)
This research is entitled "Lack of Islamic Economic Literacy Development in Sahwahita-Based Inclusion-Based Libraries (Village Need)". The purpose of this study was to find out the Sahwahita inclusive library in developing Islamic economic literacy, the obstacles of the Sahwahita inclusion library in developing Islamic economic-based literacy and the efforts made by the Sahwahita inclusive library in overcoming these obstacles. The method used is a qualitative method. The author conducted interviews with the head of the library management based on social inclusion Sahwahita. Methods of data collection using observation, interviews, and documentation. From the results of the study, it was concluded that the Sahwahita Library is still relatively new in operation which still focuses on general development activities and has not led to development activities in accordance with Islamic Shari'a. Regarding the obstacles that exist in the Sahwahita Library at this time, namely with membership, where many members have resigned because the members are students and current students who are already working out of town and many activities are carried out online due to the pandemic, many people are I still don't understand digital.